Do progressive prosecutors increase crime?: A quasi-experimental analysis of crime rates in the 100 largest counties, 2000–2020 - Petersen, Nick (Criminology & public policy, 2024)
Research summary In recent years, there has been a rise in so-called "progressive prosecutors" focused on criminal justice reforms. Although there has been considerable debate about the relationship between progressive prosecution policies and crime rates, there has been surprisingly little empirical research on the topic. Building on the limited extant research, we examined whether the inauguration of progressive prosecutors in the nation's 100 most populous counties impacted crime rates during a 21-year period (2000 to 2020). After developing an original database of progressive prosecutors in the 100 largest counties, we used heterogeneous difference-in-differences regressions to examine the influence of progressive prosecutors on crime rates. Results show that the inauguration of progressive prosecutors led to statistically higher index property (∼7%) and total crime rates (driven by rising property crimes), and these effects were strongest since 2013—a period with an increasing number of progressive prosecutors. However, violent crime rates generally were not higher after a progressive prosecutor assumed control. Policy implications Despite concerns that the election of progressive prosecutors leads to "surging" levels of violence, these findings suggest that progressive-oriented prosecutorial reforms led to relatively higher rates of property crime but had limited impact on rates of violent crime. In fact, in absolute terms, crime rates fell in jurisdictions with traditional and progressive prosecutors. Yet, relative property crime rates were greater after the inauguration of progressive prosecutors. Given that prior research shows progressive prosecutors reduce mass incarceration and racial inequalities, our findings indicate that higher property crime rates may be the price for these advancements.